A NOTE ON THE WELFARE MEASURES AND VARIOUS GOVERNMENT SCHEMES IMPLEMENTED ON THE NARIKURAVAR COMMUNITY - Ms. R. Rajpriya, Dr. S. Sudarkodi (South Eastern European Journal of Public Health, 2025)
The northern and central areas are home to the majority of the Narikuravars, a Gypsy population. Hunting is the main activity of the Narikuravar people. They are referred to as bead-people apart from that. Previously, Narikuravars were listed as members of the Most Backward Classes or De-notified Communities. They are classified as Scheduled Tribes in 2023 after years of fighting for improved access to school, work, and other necessities. The socioeconomic and educational standing of Narikuravars in the state of Tamil Nadu is examined in this research. It seeks to address the state government's programs and awards to improve the community both before and after they were granted Scheduled Tribe status. The main problems they face include poverty, illiteracy, unemployment, child marriage, school dropouts, and prejudice. Because they are ignorant of these challenges, the majority of them do not get benefits from state or federal government programs.